Analysis of household-like waste discarded by health institutions in Chile: A descriptive study - Fernanda Olive; M.Bernardita Sanhueza; Andres Giglio; Andres Ferre (The Journal of Climate Change and Health)
Background: Healthcare institutions generate significant amounts of household-like waste, with international evidence suggesting that up to 60 % is potentially recyclable. In Chile, comprehensive data on healthcare waste management and recycling practices are lacking. Objective: To assess general waste management practices in Chilean healthcare institutions and evaluate the extent of implementation of waste recycling programs across the country. Methods: We analyzed open data from the National Waste Generation Service (SINADER) for 2018–2022, focusing on healthcare institutions. Waste management practices were categorized as either disposal or valorization (recycling/pre-treatment). We evaluated the total waste volume, valorization rates, institutional characteristics, and geographical distribution of the waste management practices. Results: Of the 4,586 registered healthcare institutions in Chile, 162 (3.6 %) reported waste data, generating 291,325 tons during the study period. Only 42 institutions reported recycling activities, with the highest valorization rate of 13.6 %. Public institutions comprised 38 % of the recycling centers, with 54 % located outside the Metropolitan Region. Paper and cardboard constituted 49 % of the recycled materials, followed by organic waste (22.7 %). The national healthcare waste valorization rate increased from 0.92 % to 2.14 % between 2018 and 2022. Conclusions: This first comprehensive analysis revealed a substantial recycling gap in Chilean healthcare institutions, with current practices falling significantly below international benchmarks. The low reporting rate (3.6 %) and limited valorization highlight the urgent need for improved waste reporting systems and the implementation of comprehensive recycling programs. Achieving Chile's 2040 environmental goals will require coordinated efforts to increase healthcare waste recycling rates by at least five-fold to meet international standards.